Identification of Domestic Investment (PMDN), Exports, Government Expenditures, and Economic Growth - Aziz, Khalid Fauzi; Muslinawati, Retno (Gorontalo Development Review, 2024)
The goal of this study is to determine how domestic investment (PMDN), exports, and government spending affect economic growth. With data from BPS, the East Java Province is the subject of this study. Using the eviews application, multiple regression is the analytical technique performed. The findings revealed that whereas government spending had a favorable and very significant impact on economic growth, PMDN and exports had a positive but not statistically significant impact.